The Emerging Digital Ecosystem of Online Marketing for Startups in the Covid-19 Era: Insights from Northern Province Sri Lanka. - Shivany, S.; Dilogini, S.; Jegashini, K.; Pathmaraj, P. (Eastern University Sri Lanka., 2024)
This study investigates the emerging digital ecosystem of online marketing for startups in the Northern Province of Sri Lanka during the COVID-19 era. Using indepth interviews with 18 entrepreneurs who started their businesses during the pandemic, this study uses qualitative approaches to explore the developing digital ecosystem of internet marketing for startups during the COVID-19 era. The results show important patterns and takeaways from their experiences, emphasizing how quickly marketing tactics may be modified to meet novel obstacles. Digital marketing technologies were rapidly adopted by numerous startups, enabling live-streamed meetings and interactive content to foster client interaction. One key strategy that has evolved is community involvement. According to the data, there has been a noticeable change in the way entrepreneurs engage with their target audiences. To keep up consumer connection, social media became essential. Customized outreach, including branded email marketing and regionalized search engine optimization initiatives, has demonstrated efficacy in augmenting client retention and exposure. Brand reach and engagement were further increased through partnerships with regional influencers. Startups proved to be flexible as many shifted to online models, which resulted in a steady rise in online sales.
Keywords: Digital Marketing;Covid -19;Community engagement;Startups